Sosialisasi Pengendalian Hama Terpadu di Desa Cintaratu Kecamatan Parigi Kabupaten Pangandaran - Sudarjat Sudarjat; Syariful Mubarok; Vijaya Isnaniawardhani; Muhammad Abdilah Hasan Qonit (Universitas Mathla'ul Anwar Banten, 2020)
SOCIALIZATION OF INTEGRATED PEST MANAGEMENT IN CINTARATU VILLAGE, PARIGI DISTRICT, PANGANDARAN REGENCY. Dragon fruit plant is one of the plants that can be planted in unproductive areas such as in Pangandaran Regency, West Java Province. The problem faced in the cultivation of dragon fruit plants in the area is the high potential for pest attack. Efforts can be made to overcome these problems by increasing the insight and expertise of rural villagers through recovery both materially and in demonstration plot practices. The purpose of this activity is to increase farmers' insight into information on pests and diseases in dragon fruit plants and its integrated handling technology. This activity was carried out in Cintaratu Village, Parigi District, Pangandaran District with an active participatory method in the form of counseling on pest attacks on dragon fruit plants as well as integrated pest management technologies on dragon fruit plants. This program has succeeded in informing about pest attacks and integrated handling technologies on dragon fruit plants in coastal areas. This success was shown based on the responses of enthusiastic extension participants and their interest in applying the technology to the cultivation of dragon fruit plants that they manage. The results of this activity can be seen in the increase in yields from the dragon orchards managed by local residents.